PERBEDAAN POLA KONSUMSI REMAJA PUTERI OVERWEIGHT DAN NORMAL DI SMA NEGERI 1 SIBORONGBORONG KOTA MEDAN TAHUN 2017 - Maria Yensiska Siahaan; Martha Irene Kartasurya; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Overweight in adolescence will have an impact on the incidence of non-communicable diseases in adulthood. Theoverweight incident in SMA Negeri 1 Siborongborong is quite high around 60% based on preliminary study results. This study aimed to determine differences in consumption patterns of overweight and normal in SMA Negeri 1 Siborongborong Medan. Theyresearchwas anobservational study with a cross sectional approach. Research subjects were 80 female teenagers aged 15-18 years, which consisted of overweight 40 student (BMI z scores >+1 SD) and 40normal female students. Subject selection was done by purposive sampling. Data collection was done by anthropometric measurement: height, weight, waist circumference, and semi quantitative Food Frequency Questionaire.Data analysisusing Mann Whitney test.The results showed that overweight nutritional status group had energy sufficiency level of114,60% ± 66,54,proteinadequacy level92,74%±7,74, fat intake 50,60 g ± 36,60,fiber intake 14,15g ± 9,98,cholesterol intake160,7 g ± 140,29, physical activity levels1,33 ± 0.21, The normal female students had energy sufficiency level of93,87% ± 19,96,level ofadequacyprotein 88,33% ± 11,36, fat intake 60,78 g ± 42,12, fiber intake11,97g ± 7,02,cholesterol intake286,4 g ± 544,8, physical activity 1.80 ± 0.23. There were no difference in the level ofenergyadequacy p=0,054,proteinadequacy p=0,059, between overweight andnormal nutritional status. There was no difference in fat intake p=0,225, fiber intake p=0,579, andcholesterol intake p=0,079 between overweight and normal nutritional status. There were differences physical activity between overweight and normal nutritional status p=0.000.Suggestions given for the school to increase the physical activity level of the students.